Ambiguous immigrants? Examining the changing status of the English in New Zealand. Issue 3 (July 2014) - Pearson, David
Abstract Drawing on a qualitative interview‐based study of English migrants in New Zealand, this article examines, if and how, overseas migration triggers national sentiments that were previously relatively amorphous in their country of origin. In those cases where this occurs, it analyses the diverse and contextual orientations migrants display, and discusses the empirical and analytic challenges posed when seeking to conceptualise a category of persons that have been described as 'ambiguous immigrants'. The study concludes that research on this ambiguity contributes to debates about the relationship between dominant ethnicity and national identity while highlighting the simplicities of many concepts used to describe and analyse 'the English'.